Microplastics in two fish species from Prydz Bay and King George Island: Occurrence, characteristics and risk assessment - Kexin Zhang; Zhiwei Gao; Peng Ju; Yunmei Sun; Jie Zhang; Yan Gu; Chengjun Sun; Haitao Ding (Marine Pollution Bulletin, 2026)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

CPTU-Based Offshore Wind Monopile Rigid Bearing Mechanism Analysis - Jie Zhou; Renjie Gu; Panpan Shen; Chengjun Liu; Zeyao Li; Kefan Zhu; Zhenming Shi (Journal of Marine Science and Engineering, 2025)
With the development of the offshore wind industry in China, the amount of offshore wind turbines has increased rapidly. Large-diameter steel monopile foundations of offshore wind turbines have been widely adopted in China with lots of marine clay located. However, the conventional offshore wind monopile bearing capacity prediction from the American Petroleum Institute (API) based on the small-diameter flexible pile field test is inaccurate with the rigid mechanism of large-diameter monopile causing economically loss. The piezocone penetration test (CPTU) is a common marine in situ test to exactly acquire soil parameters. Therefore, a CPTU-based offshore wind monopile rigid mechanism inference method is proposed. A creative numerical offshore wind power monopile and CPTU combined model is established through COMSOL. A self-compiling parameter function is applied to soil modeling and an innovative mobile boundary function is created to simulate CPTU penetration. Through the model, real-time CPTU data can be acquired when monopile is applied with different horizontal loads. The peripile soil stress change can be timely detected by CPTU. Through CPTU data, the monopile rigid bearing mechanism is verified. A rigid rotation center is found at the 60% point of the inserted monopile. The method is an important foundation for the next step of monopile bearing capacity research.

Visualizing hydrogen peroxide and hydrogen sulfide fluctuations in living cells via dynamic-reversible fluorescent probes - Jinzhu Gao; Rongchen Wang; Kai Yin; Tianli Zhu; Jie Sun; Chengjun Dong; Xuemei Dong; Mengting Zhao; Xianfeng Gu; Chunchang Zhao (Chemical Engineering Journal, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.